2020
DOI: 10.1002/ppul.24914
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles influence the pulmonary arterial extracellular matrix in congenital diaphragmatic hernia

Abstract: Objective Abnormal pulmonary vasculature directly affects the development and progression of congenital diaphragmatic hernia (CDH)‐associated pulmonary hypertension (PH). Though overarching structural and cellular changes in CDH‐affected pulmonary arteries have been documented, the precise role of the extracellular matrix (ECM) in the pulmonary artery (PA) pathophysiology remains undefined. Here, we quantify the structural, compositional, and mechanical CDH‐induced changes in the main and distal PA ECM and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Our systematic searches yielded a total of 1167 records (Figure 1 ). Following level 1 screening of titles and abstracts, 434 articles underwent level 2 full‐text screening which resulted in a total of 52 studies included for our systematic review (Ahn et al., 2018 ; Aliotta et al., 2017 , 2016 ; Bandeira et al., 2018 ; Braun et al., 2018 ; Chaubey et al., 2018 ; Chen et al., 2014 , 2019 , 2020 ; Choi et al., 2014 ; Cruz et al., 2015 ; de Castro et al., 2017 ; Deng et al., 2020 ; Dinh et al., 2020 ; Fang et al., 2020a , 2020b ; Gao et al., 2020 ; Hao et al., 2019 ; Harrell et al., 2020 ; Hogan et al., 2019 ; Huang et al., 2019 ; Khatri et al., 2018 ; Kim et al., 2020 ; Klinger et al., 2020 ; Lee et al., 2012 ; Lei et al., 2020 ; Li et al., 2015 , 2019a , 2019b , 2020 ; Liu et al., 2018 , 2019a , 2019b ; Mansouri et al., 2019 ; Maremanda et al., 2019 ; Monroe et al., 2020 ; Monsel et al., 2015 ; Porzionato et al., 2019 ; Potter et al., 2018 ; Silva et al., 2019 ; Stone et al., 2017 ; Tang et al., 2017 ; Varkouhi et al., 2019 ; Wang et al., 2020 ; Willis et al., …”
Section: Resultsmentioning
confidence: 99%
“…Our systematic searches yielded a total of 1167 records (Figure 1 ). Following level 1 screening of titles and abstracts, 434 articles underwent level 2 full‐text screening which resulted in a total of 52 studies included for our systematic review (Ahn et al., 2018 ; Aliotta et al., 2017 , 2016 ; Bandeira et al., 2018 ; Braun et al., 2018 ; Chaubey et al., 2018 ; Chen et al., 2014 , 2019 , 2020 ; Choi et al., 2014 ; Cruz et al., 2015 ; de Castro et al., 2017 ; Deng et al., 2020 ; Dinh et al., 2020 ; Fang et al., 2020a , 2020b ; Gao et al., 2020 ; Hao et al., 2019 ; Harrell et al., 2020 ; Hogan et al., 2019 ; Huang et al., 2019 ; Khatri et al., 2018 ; Kim et al., 2020 ; Klinger et al., 2020 ; Lee et al., 2012 ; Lei et al., 2020 ; Li et al., 2015 , 2019a , 2019b , 2020 ; Liu et al., 2018 , 2019a , 2019b ; Mansouri et al., 2019 ; Maremanda et al., 2019 ; Monroe et al., 2020 ; Monsel et al., 2015 ; Porzionato et al., 2019 ; Potter et al., 2018 ; Silva et al., 2019 ; Stone et al., 2017 ; Tang et al., 2017 ; Varkouhi et al., 2019 ; Wang et al., 2020 ; Willis et al., …”
Section: Resultsmentioning
confidence: 99%
“…Monroe et al. showed that EVs derived from bone marrow MSCs have a beneficial effect on the extracellular matrix (ECM) of the pulmonary arteries of rat fetuses with CDH, with attenuation of ECM enzymatic activity, rescue of ECM composition, and restoration of medial wall thickness 74 . Furthermore, Zhaorigetu et al.…”
Section: Ev Effects On Pulmonary Vascular Developmentmentioning
confidence: 99%
“…[95][96][97] Accordingly, the reparative potential of EVs and their influence on cell-ECM interactions has been the subject of research aiming to improve cardiac recovery following MI. 98,99 However, the effects of ECM composition and stiffness on EV secretion are poorly understood. Future work should examine if the myocardial ECM composition influences EV yield and also EV cargo type under ischemic conditions.…”
Section: The Future Of Research On Cell-ecm Interactions and Cardiac Repairmentioning
confidence: 99%